“Nós somos raiz do lugar” produção do espaço na Comunidade Quilombola São José do Barro Vermelho - Renata Guimarães Vieira (2018)
From the modernity narrative, Europe had shaped a symbolic and material world which expands itself beyond its origin continent. The colonial meeting has formed modern narrative and it has also another face: the coloniality. The coloniality is based in the domination and exploitation of the Other, mainly through racism and capitalism. The development is, currently, a narrative extensively used by Brazilian State. On such narrative are laid down the coloniality preconceptions. The production of space by the State is committed to such preconceptions, which becomes more evident when there are conflicts between this State and traditional communities. Based on these concepts, this work aims to reflect about the production of space promoted by the State and by the Quilombola Community São José do Barro Vermelho. Then, the work seeks to comprehend the conflict between the dwellers and the creation of the State Park of Serra das Araras, overlaid to the land occupied and used by the community. Finally, I conclude that the community assumes a behavior of resistance against the homogenization of the space and the life proposed by the modernity-coloniality, producing spaces to diversity which dialogues with Lefebvre‟s notion of differential space.